If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3p+2)-5(6p-1)=2(p-8)-6(7p-4)+4p
We move all terms to the left:
4(3p+2)-5(6p-1)-(2(p-8)-6(7p-4)+4p)=0
We multiply parentheses
12p-30p-(2(p-8)-6(7p-4)+4p)+8+5=0
We calculate terms in parentheses: -(2(p-8)-6(7p-4)+4p), so:We add all the numbers together, and all the variables
2(p-8)-6(7p-4)+4p
We add all the numbers together, and all the variables
4p+2(p-8)-6(7p-4)
We multiply parentheses
4p+2p-42p-16+24
We add all the numbers together, and all the variables
-36p+8
Back to the equation:
-(-36p+8)
-18p-(-36p+8)+13=0
We get rid of parentheses
-18p+36p-8+13=0
We add all the numbers together, and all the variables
18p+5=0
We move all terms containing p to the left, all other terms to the right
18p=-5
p=-5/18
p=-5/18
| 2x(-5)+3=29-4x | | 3x+1÷2x-2=7 | | 15(a-4)-2(a-9)+5(a+6)=0 | | 3x+1÷2x2=7 | | 1/11y-4=-9 | | 8^x*16^x=4^72-x | | 3x-6-9x=-x+8 | | 3x+42+9x-6=180 | | -x-2x-1=3x+4+1= | | 3x+3=3x+14 | | 3/5x+6=13 | | 2x3+6x=15x2-7 | | 2^2x+2^2x+1-8=0 | | X/3=(2+x)/4 | | 2y+3=21-4y | | 2x-5+(8/x)=0 | | 2x+6=7x14 | | 6x8=x | | -2x²+5x-3=0 | | 3^3x+2=243 | | 5-2=-5x/2 | | 2-(3x-7/4)+x+17/5=0 | | 21–x=4x. | | 1-2x/5=2-x/2 | | 4D^4+4D^3-3D^2-2D+1)y=0 | | -27/x+0.5x+1.5=0 | | x2+15x-56.25=0 | | x2-7x-34=10 | | 11m-6m=30 | | 10x-6x2=0 | | 2x-7=3x-20 | | x²-4x+5=0 |